ANKS4B Restricts Replication of Zika Virus by Downregulating the Autophagy - Lin, Quanshi; Zhou, Shili; Huang, Yanxia; Huo, Zhiting; Chen, Cancan; Luo, Xin; He, Junfang; Liu, Chao; Zhang, Ping (Frontiers in Microbiology, 2020)
Infection of Zika virus (ZIKV) has become a severe threaten to global health while no specific drug is available. In this study, we explored the relationship between ZIKV and a cellular protein, ankyrin repeat and sterile motif domain containing 4b (ANKS4B). Our data revealed that the expression of ANKS4B in cultured cells and in neonatal mice was downregulated by ZIKV infection. The reduction of ANKS4B upon ZIKV infection was caused by decrease of two hepatocyte nuclear factors HNF1alpha and HNF4alpha. Through CRISPR/Cas9 gene editing system, we generated two ANKS4B knockout (KO) cell clones in A549 and Huh7 cells respectively. In the ANKS4B-KO cells, the viral replication levels including viral RNA, protein, and titer were significantly enhanced, which was reversed by trans-complementation of ANKS4B. ANKS4B did not affect the viral entry step, but impaired the autophagy induced by ZIKV infection. Furthermore, our data showed that inhibition of autophagy led to similar replication levels of ZIKV in ANKS4B-sufficient and ANKS4B-deficient cells, suggesting the antiviral effect of ANKS4B relied on its modulation on the autophagy. Therefore, our work identified ANKS4B as a new restriction factor of ZIKV.